2017
DOI: 10.1097/bco.0000000000000480
|View full text |Cite
|
Sign up to set email alerts
|

Combined adductor canal and sciatic nerve block compared with local intraarticular infiltration analgesia for total knee arthroplasty: a prospective blinded randomized controlled study

Abstract: Background: A combined adductor canal block and sciatic nerve block is an efficient way to obtain postoperative analgesia after total knee replacement that spares the motor power of the femoral nerve. This is a prospective controlled randomized study comparing the efficacy of local infiltrative analgesia (LIA) to a combined adductor canal block and sciatic nerve block (CNB). Methods: Seventy-five patients were included and randomized to two groups. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
0
1
Order By: Relevance
“…Only one clinical trial compared both blocks (ACB+SNB) with LAI for pain management after TKR, moreover, results of our study contradict this study [21], which showed that combined ACB with SVB was comparable in analgesic efficacy to LAI.…”
Section: Discussioncontrasting
confidence: 56%
“…Only one clinical trial compared both blocks (ACB+SNB) with LAI for pain management after TKR, moreover, results of our study contradict this study [21], which showed that combined ACB with SVB was comparable in analgesic efficacy to LAI.…”
Section: Discussioncontrasting
confidence: 56%